Factors Affecting the Adherence of People Living with HIV/AIDS on Antiretroviral Treatment in Tasikmalaya City - Iis Sopiah Suryani; Lina Marlina; Ana Ikhsan Hidayatulloh; Ai Rahmawati (Poltekkes Kemenkes Palu, 2025)
The incidence of HIV/AIDS in Indonesia, including in West Java and Tasikmalaya City, continues to rise. In Tasikmalaya City alone, 345 cases have been recorded. Antiretroviral (ARV) therapy has revolutionized HIV treatment, but optimal adherence—ideally 100%—is essential to prevent drug resistance. However, adherence among people living with HIV/AIDS (PLWHA) in Tasikmalaya remains suboptimal, increasing the risk of treatment failure and resistance. This study employed a cross-sectional correlational design involving 62 PLWHA who actively participated in monthly meetings organized by the AIDS Countermeasures Commission (KPA) in Tasikmalaya. Participants were selected using purposive sampling. Data were collected using a validated questionnaire for treatment adherence and a researcher-developed instrument to assess additional variables. Factors found to influence ARV treatment adherence included age, gender, educational background, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-confidence. Among these, perceived barriers were identified as the most dominant factor affecting adherence (OR = 16.9). Although limited by a small sample size, this study highlights several psychosocial and demographic factors that influence ARV adherence among PLWHA. Addressing perceived barriers should be a priority in interventions aimed at improving adherence and preventing drug resistance.